Microstructure–properties relationship in ethylene-propylene diene monomer (EPDM)/nitrile butadiene rubber (NBR)/halloysite nanotubes (HNTs) nanocomposites - Seyed Mohamad Reza Paran (17541846) (2023)
Structure–properties relationship in complex rubber nanocomposites is a key for enlarging the performance window. Herein, halloysite nanotubes (HNTs) are added at variable content to ethylene-propylene diene monomer (EPDM)/nitrile butadiene rubber (NBR) rubber blends compatibilized with maleic anhydride grafted HNTs to evaluate cure characteristics, along with microstructure, and mechanical and swelling behavior. The crosslinking rate increased by HNTs loading, but the scorch time decreased. Moreover, a 45% rise in tensile strength was observed for systems containing 10 wt% HNTs. SEM and TEM micrographs revealed a rough fracture surface with proper dispersion of HNT within EPDM/NBR. The modulus of EPDM/NBR/HNTs nanocomposites is theoretically estimated by modified Kolarik model, demonstrating a good agreement with experimental value. Dynamic mechanical thermal analysis (DMTA) revealed a higher storage modulus up to 2.27 GPa with the introduction of HNTs into EPDM/NBR compound. Correspondingly, lower solvent uptake (decreased by 38%) is reported. Thermogravimetric analysis (TGA) revealed higher thermal stability for highly-loaded systems. Other Information Published in: Polymer Bulletin License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00289-023-04723-7